Critical assessment and thermodynamic modeling of the Cu–Fe–O–Si system. (September 2017) - Hidayat, Taufiq; Shishin, Denis; Decterov, Sergei A.; Jak, Evgueni
Abstract: The present study is the first Calphad-type assessment of the Cu–Fe–O–Si system. All relevant thermodynamic and phase equilibrium data have been critically evaluated to produce a thermodynamic database describing the Gibbs energies of all phases in the system. The predictive range of the database covers all conditions of pyrometallurgical production of copper in terms of temperature and oxygen partial pressure. Liquid oxide slag and liquid metal phases have been described using two separate solution models, both developed within the framework of the Modified Quasichemical Formalism. Slag model is expressed as [Cu +, Fe 2+, Fe 3+, Si 4+ ][O 2- ] and metal model is expressed as (Cu I, Fe II, O II ). They are internally consistent with the models for fcc–Cu, fcc–Fe, bcc–Fe, spinel, wüstite, CuFeO2, Cu2 O, Fe2 SiO4, Fe2 O3 and SiO2 obtained in the previous optimizations of the Cu–O, Fe–O, Cu–Fe, Cu–Fe–O, Cu–O–Si, Fe–O–Si sub-systems.